Health Insurance Theory: The Case of the Vanishing Welfare Gain - John A. Nyman (University of Minnesota, Center for Economic Research, 2003)
This paper presents theory that an important source of value is missing from conventional theory of the demand for health insurance, namely, the effect of the transfer of income (from those who purchase insurance and remain healthy to those who purchase insurance and become ill) on purchases of medical care. Because the portion of moral hazard that is attributable to income is welfare increasing and would replace some of moral hazard that is spuriously deemed to be welfare decreasing, the new theory suggests that the value of health insurance has been dramatically undervalued. Implications for policy are outlined.
Keywords: 330; Krankenversicherung; Nachfrage; Moral Hazard; Gesundheitswesen; Wohlfahrtseffekt; Theorie